IgA Levels among Type 2 Diabetic and Non-Diabetic Patients with Periodontitis: A Prospective Clinical Study - Palwankar, Pooja; Jain, Saumya; Pandey, Ruchi; Mahesh, Shakila (European Journal of Dentistry, 2022)
Objectives To estimate gingival crevicular immunoglobulin A(IgA) using enzyme-linked immunosorbent assay (ELISA) among type II diabetic patients with periodontitis.Materials and Methods A non-randomized study was done of 40 periodontitis subjects with a mean age of 50 years and were recruited into two groups, Group A (Type II controlled diabetics with HbA1c < 7%) and Group B (non-diabetics with HbA1c between 4 and 6%). Both the groups underwent nonsurgical periodontal therapy (NSPT). The clinical parameters were recorded at baseline, 1, and 3 months. GCF sample was collected for the estimation of crevicular IgA at baseline and at 3 months.Statistical Analysis Results were analyzed using parametric tests paired t-test and Student's t-test for every assessment point. The level of significance was set at p < 0.05.Results Difference in IgA levels and clinical parameters was seen between diabetic and non-diabetic groups, which was statistically significant.Conclusion Changes in crevicular IgA levels in patients with diabetic periodontitis can be used as a novel biomarker in assessing the inflammatory status.
Keywords: Enzyme linked immunosorbent assay; Immunoglobulin A; nonsurgical periodontal therapy; gingival crevicular fluid; diabetes mellitus; diabetes biomarkers